第 11 课 RD Sharma 解决方案-第 23 章直线-练习 23.11
问题1:证明以下三行是并发的:
(i) 15x – 18y + 1 = 0、12x + 10y – 3 = 0 和 6x + 66y – 11 = 0
(ii) 3x – 5y – 11 = 0, 5x + 3y – 7 = 0 和 x + 2y = 0
解决方案:
(i) 15x – 18y + 1 = 0, 12x + 10y – 3 = 0 and 6x + 66y – 11 = 0
Given:
15x – 18y + 1 = 0 …… (i)
12x + 10y – 3 = 0 …… (ii)
6x + 66y – 11 = 0 …… (iii)
Solving equation (i) and (ii), we get,
From equation (i) we get,
x = (18y – 1)/15
Now substituting the value of x in equation (ii)
12 [(18y – 1)/15] + 10y – 3 = 0
216y – 12 + 150y – 45 = 0
366y = 57
y = 57/366 = 19/122
Now substituting the value of y in x i.e.
x = (18y – 1)/15
x = (18(19/122) – 1)/15
x = (342 – 122) / (122 × 15)
x = (342 – 122) / 1730
x = 220/1730
x= 22/173
Now substituting the value of x and y in equation (iii), we get,
6(22/173) + 66(19/122) – 11 = 0
(6 × 22 ×122) + (66 × 19 × 173) – (11 × 173 × 122) = 0
320 – 2052 + 732 = 0
0 = 0
Therefore, the given lines are concurrent.
(ii) 3x – 5y – 11 = 0, 5x + 3y – 7 = 0 and x + 2y = 0
Given:
3x − 5y − 11 = 0 …… (i)
5x + 3y − 7 = 0 …… (ii)
x + 2y = 0 …… (iii)
Solving equation (ii) and (iii), we get,
From equation (iii) we get,
x = -2y
Now substituting the value of x in equation (ii)
5(-2y) + 3y – 7 = 0
-10y + 3y – 7 = 0
-7y = 7
y = -1
Now substituting the value of y in x i.e.
x = -2y
x = -2(-1)
x = 2
Now substituting the value of x and y in equation (i), we get,
3(2) − 5(-1) − 11 = 0
6 + 5 – 11 = 0
11 – 11 = 0
0 = 0
Therefore, the given lines are concurrent.
问题 2:对于λ的值,2x – 5y + 3 = 0、5x – 9y + λ = 0 和 x – 2y + 1 = 0 三行并发?
解决方案:
Given:
2x − 5y + 3 = 0 …… (i)
5x − 9y + λ = 0 …… (ii)
x − 2y + 1 = 0 …… (iii)
Solving equation (i) and (iii), we get,
From equation (i) we get,
2x = 5y – 3
x = (5y – 3)/2
Now substituting the value of x in equation (iii)
[(5y – 3)/2] – 2y + 1 = 0
5y – 3 – 4y + 2 = 0
y = 1
Now substituting the value of y in x i.e.
x = (5y – 3)/2
x = (5 – 3)/2
x = 2/2
x = 1
Now substituting the value of x and y in equation (ii), we get,
5(1) – 9(1) + λ = 0
5 – 9 + λ = 0
λ = 4
Therefore, the value of λ is 4.
问题3:求直线y = m 1 x + c 1 ,y = m 2 x + c 2和y = m 3 x + c 3可能在一点相交的条件。
解决方案:
Given:
m1x – y + c1 = 0 …… (1)
m2x – y + c2 = 0 …… (2)
m3x – y + c3 = 0 …… (3)
Solving equation (i) and (ii), we get,
m1x – y + c1 = m2x – y + c2
m1x + c1 = m2x + c2
m1x – m2x = c2 – c1
x(m1 – m2) = c2 – c1
x = (c2 – c1)/(m1 – m2)
Now substituting the value of x in equation (i)
y = m1[(c2 – c1)/(m1 – m2)] + c1
y = m1c2 – m1c1 + m1c1 – m2c1
y = m1c2 – m2c1
Now substituting the value of x and y in equation (iii), we get,
m3x – y + c3 = 0
y = m3x + c3
m1c2 – m2c1= m3[(c2 – c1)/(m1 – m2)] + c3
m12c2 – m1m2c1 + m1m2c2 – m22c1 = m3c2 – m3c1 + m1c3 – m2c3
m12c2 – m1c3 – m22c1 + m2c3 – m3c2 + m3c1 = 0
m1(c2 – c3) + m2(c3 – c1) + m3(c1 – c2) = 0
Therefore, the required condition is m1(c2 – c3) + m2(c3 – c1) + m3(c1 – c2) = 0
问题 4:如果线 p 1 x + q 1 y = 1, p 2 x + q 2 y = 1 和 p 3 x + q 3 y = 1 是并发的,证明点 (p 1 , q 1 ), (p 2 , q 2 ) 和 (p 3 , q 3 ) 是共线的。
解决方案:
Given:
p1x + q1y = 1 …… (i)
p2x + q2y = 1 …… (ii)
p3x + q3y = 1 …… (iii)
Solving equation (i) and (ii), we get,
From equation (i) we get,
x = (1 – q1y)/p1
Now substituting the value of x in equation (ii)
p2[(1 – q1y)/p1] + q2y = 1
p2 – p2q1y + p1q2y = p1
y(p1q2 – p2q1) = p1 – p2
y = (p1 – p2)/(p1q2 – p2q1)
Now substituting the value of y in x i.e.
x = (1 – q1y)/p1
x = (1 – q1[(p1 – p2)/(p1q2 – p2q1)])/p1
Now substituting the value of x and y in equation (iii), we get,
p3[(p1q2 – p2q1 – q1(p1 – p2)(p1q2 – p2q1))] + q3p1(p1 – p2) = 1
(p1p3q2 – p2p3q1 – p1p3q1 + p2p3q1)(p1q1 – p2q1) + q3p1(p1 – p2) = 1
(p1p3q2 – p1p3q1)(p1q2 – p2q1) + q3p12 – q3p1p2 = 1
p12p3q22 – p1p2p3q1q2 – p12p3q1q2 + p1p2p3q12 + q3p1p2 = 1 …… (iv)
Also, if we assume points (p1, q1)(p2, q2)(p3, q3) are collinear
Therefore,
p1(q2 – q3) + p2(q3 – q1) + p3(q1 – q3) = 0
Now from equation (iv) we get,
p1[p1p3q22 – p2p3q1q2 – p1p3q1q2 + p2p3q12 + q3p2] = 1
p1[p3q2(p1q2 – p2q1) – p3q1(p1q2 – p2q1) + q3(p1 – p2)] = 1
Therefore, the given points, (p1, q1), (p2, q2) and (p3, q3) are collinear.
问题 5:证明直线 L 1 = (b + c)x + ay + 1 = 0, L 2 = (c + a)x + by + 1 = 0 和 L 3 = (a + b)x + cy + 1 = 0 是并发的。
解决方案:
Given:
L1 = (b + c)x + ay + 1 = 0 …… (i)
L2 = (c + a)x + by + 1 = 0 …… (ii)
L3 = (a + b)x + cy + 1 = 0 …… (iii)
Solving equation (i) and (ii), we get,
From equation (i) we get,
y = (-1 – (b + c)x)/a
Now substituting the value of y in equation (ii)
(c + a)x + b[(-1 – (b + c)x)/a] + 1 = 0
(c + a)x + b[(-1 – (bx + cx)/a] + 1 = 0
cx + ax + b[(-1 – (bx + cx)/a] + 1 = 0
acx + a2x – b – b2x + bcx + a = 0
x(ac + a2 – b2 + bc) = b – a
x(c(a – b) + (a – b)(a + b)) = b – a
x(a – b)(c + a + b) = -(a – b) [Dividing both side by (a – b)]
x(c + a + b) = -1
x = -1/(a + b + c)
Now substituting the value of x in y i.e.
y = (-1 – (b + c)x)/a
y = (-1 – (b + c)[-1/(a + b + c)])/a
y = (-(a + b + c) + b + c)/a(a + b + c)
y = (-a – b – c + b + c)/a(a + b + c)
y = (-a)/a(a + b + c)
y = -1/(a + b + c)
Now substituting the value of x and y in equation (iii), we get,
(a + b)[-1/(a + b + c)] + c[-1/(a + b + c)]+ 1 = 0
-a – b – c + a + b + c = 0
0 = 0
Therefore, the given lines are concurrent.
问题 6:如果三行 ax + a 2 y + 1 = 0、bx + b 2 y + 1 = 0 和 cx + c 2 y + 1= 0 是并发的,证明三个常数 a、 b、c 相等。
解决方案:
Given:
ax + a2y + 1 = 0 …… (i)
bx + b2y + 1 = 0 …… (ii)
cx + c2y + 1= 0 …… (iii)
Solving equation (i) and (ii), we get,
From equation (i) we get,
x = (-1 – a2y)/a
Now substituting the value of x in equation (ii)
b[(-1 – a2y)/a] + b2y + 1 = 0
-b – a2by + ab2y + a = 0
aby(b – a) = b – a [Dividing both side by (b – a)]
aby = 1
y = 1/ab
Now substituting the value of y in x i.e.
x = (-1 – a2y)/a
x = (-1 -a2(1/ab))/a
x = (-b – a)/ba
Now substituting the value of x and y in equation (iii), we get,
c[(-b – a)/ba] + c2(1/ab) + 1 = 0
-bc – ac + c2 + ab = 0
c(c – b) – a(c – b) = 0
(c – b)(c – a) = 0
c – b = 0
c = b
or
c – a = 0
c = a
Therefore, at least two of three constants a, b, c are equal.
问题 7:如果 a,b,c 在 AP 中,证明直线 ax + 2y + 1 = 0, bx + 3y + 1 = 0 和 cx + 4y + 1 = 0 是并发的。
解决方案:
Given if a, b, c are in A.P.
Thus, b – a = c – b
2b = a + c [Common difference] …… (i)
Also given:
ax + 2y + 1 = 0 …… (ii)
bx + 3y + 1 = 0 …… (iii)
cx + 4y + 1 = 0 …… (iv)
Solving equation (ii) and (iii), we get,
From equation (ii) we get,
x = (-1 – 2y)/a
Now substituting the value of x in equation (iii)
b[(-1 – 2y)/a] + 3y + 1 = 0
-b – 2by + 3ay + a = 0
y(3a – 2b) = b – a
y = (b – a)/(3a – 2b)
Now substituting the value of y in x i.e.
x = (-1 – 2y)/a
x = (-1 – 2[(b – a)/(3a – 2b)])/a
x = (-(3a – 2b) – 2b + 2a)/a(3a – 2b)
x = -1/(3a – 2b)
Now substituting the value of x and y in equation (iv), we get,
c[-1/(3a – 2b)] + 4[(b – a)/(3a – 2b)] + 1 = 0
-c + 4b – 4a + 3a – 2b = 0
-a + 2b – c = 0
From equation (i) we know, 2b = a + c,
Thus, -a + a + c – c = 0
0 = 0
Therefore, the given lines are concurrent.